Wheat responses to stresses caused by low light intensity and/or water excess in the soil. I. Greenhouse testing - Sheeren, Pedro Luiz; de Carvalho, Fernando Irajá Félix; Federizzi, Luiz Carlos (Pesquisa Agropecuaria Brasileira, 1995)
The experiment was carried out in 1987 in the greenhouse at the Faculty of Agronomy of the Federal University of Rio Grande do Sul, in Porto Alegre, RS. The objective of this work was to assess the effect of stresses caused by water excess in the soil and by light reduction on 12 wheat (Triticum aestivum L.) genotypes. Significant reductions were observed in the dry matter weight and in the ramification of roots of plants submitted to the treatment of water excess in the soil, while the treatments including shading caused significant reduction in above-ground wheat plant parts. Cultivar IAC 5-Maringá and lines PF 85845 and PF 853048 were the genotypes least affected by applied stresses.